2016
DOI: 10.1111/tpj.13302
|View full text |Cite
|
Sign up to set email alerts
|

The developmental transcriptome atlas of the biofuel crop Camelina sativa

Abstract: SUMMARYCamelina sativa is currently being embraced as a viable industrial bio-platform crop due to a number of desirable agronomic attributes and the unique fatty acid profile of the seed oil that has applications for food, feed and biofuel. The recent completion of the reference genome sequence of C. sativa identified a young hexaploid genome. To complement this work, we have generated a genome-wide developmental transcriptome map by RNA sequencing of 12 different tissues covering major developmental stages d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 70 publications
3
63
1
Order By: Relevance
“…Unlike wheat, Camelina has three similar subgenomes that are generally expressed, indicating the existence of an important functional gene redundancy (Kagale et al, 2014(Kagale et al, , 2016. Our work shows that CRISPR-Cas9 could efficiently bypass this limitation by quickly isolating triple homozygous mutants.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Unlike wheat, Camelina has three similar subgenomes that are generally expressed, indicating the existence of an important functional gene redundancy (Kagale et al, 2014(Kagale et al, , 2016. Our work shows that CRISPR-Cas9 could efficiently bypass this limitation by quickly isolating triple homozygous mutants.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of csfad2-2 mutation on OAI could even be observed in the heterozygous state, indicating the importance of allele dosage for FAD2 activity ( Figure S4). It was reported that Camelina subgenome 3 (CsG3) was globally more expressed than the two other subgenomes (Kagale et al, 2016). CsFAD2-2 belongs to CsG3, and indeed, its expression is higher in maturing seeds compared to the two other homeologous genes ( Figure S5).…”
Section: Mutations In Fad2 Genes Modified the C18 Desaturation Profilmentioning
confidence: 91%
See 3 more Smart Citations